PENERAPAN MODEL BERMAIN PERAN (ROLE PLAYING) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 60 DURI - Nurcahaya Nurcahaya; Erlisnawati Erlisnawati; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the lack of civics student learning outcomes, as seen from the average value of students is 59.17. Of the 24 students who achieve grades above KKM just 6 students (25%), while students who have not yet reached KKM many as 18 people (75%), the value specified KKM is 70. Based on these problems is necessary to study a class action by applying the model role Playing. This research aims to improve learning outcomes Civics class students V A SD Negeri 60 Duri school year 2014/ 2015 the number of students 24 people consisting of 13 men and 11 women. This study was conducted by two cycles. At each cycle I and II consist of three meetings, which consists of two face to face meetings and one times daily test at the end of the cycle. With Role Playing models approach is applied, it can improve learning outcomes Civics students, it can be seen from the increase in student learning outcomes from the base score is an average of 59.17, an increase of 9.85% to 65 in the first cycle, and the cycle II increased by 45.77% to 86.25. The percentage of teacher activity also increased, as seen from the percentage of the activity of teachers in the first cycle the first meeting 60% increase in the second meeting to 75%, in the first meeting of the second cycle increased to 85% and in the second meeting to 95%. Based on the results of this study concluded that the application of the Model Role Playing, can improve learning outcomes civics class students VA SD Negeri 60 Duri.Key Words : Usage Model Role Playing, Civics Student Learning Outcomes.